Literature Review: The Role of Adipose Stem Cell Secretome In Caspase-3 Regulation and Endothelial Cell Density Preservation in Corneal Regeneration Post-Phacoemulsification - Perwitasari, Birgitta Henny; Komaratih, Evelyn; Hermawan, Dicky (Journal of Neonatal Surgery, 2025)
Phacoemulsification is the most widely used surgical technique for cataract removal; however, it poses risks of corneal endothelial damage, leading to complications such as corneal edema and vision impairment. The corneal endothelium plays a crucial role in maintaining corneal transparency, yet it has limited regenerative capacity. Endothelial cell loss following phacoemulsification results from mechanical trauma, oxidative stress, and apoptosis, with caspase-3 acting as a key mediator of programmed cell death. Excessive apoptosis leads to a critical reduction in endothelial cell density (ECD), causing corneal decompensation and potential vision loss. Current treatments, including endothelial keratoplasty, are limited by donor shortages and surgical risks. Stem cell-derived secretomes, particularly from adipose-derived stem cells (ASCs), have emerged as a promising therapeutic approach for corneal endothelial repair. ASC secretomes contain bioactive molecules such as growth factors and cytokines that promote endothelial cell survival, reduce apoptosis by downregulating caspase-3, and enhance tissue regeneration. Preclinical studies suggest that ASC secretomes may effectively support endothelial recovery post-phacoemulsification. This literature review explores the mechanisms of endothelial damage, the role of apoptosis in corneal cell loss, and the therapeutic potential of ASC secretomes as a novel intervention for protecting and restoring corneal endothelium following cataract surgery. Additionally, the use of New Zealand white rabbits as an animal model for studying endothelial regeneration is discussed.